THE MAIN COMPONENTS OF A SMART CITY AND THEIR MANAGEMENT - Потапенко, Софія (SWorldJournal, 2022)
The work is devoted to the study of the development of smart cities in Switzerland, mostly the smart city of Zurich. The article considers the features of various components and directions of smart city development, such as smart citizens, smart governmen